65.9k views
1 vote
3(2 – 0.9h)  (1.3h  4)

User Albo
by
5.4k points

1 Answer

4 votes

If you are solving for "h" here you go.

Simplifying

3(2 + -0.9h) + (-1.3h + -4) = 0

(2 * 3 + -0.9h * 3) + (-1.3h + -4) = 0

(6 + -2.7h) + (-1.3h + -4) = 0

Reorder the terms:

6 + -2.7h + (-4 + -1.3h) = 0

Remove parenthesis around (-4 + -1.3h)

6 + -2.7h + -4 + -1.3h = 0

Reorder the terms:

6 + -4 + -2.7h + -1.3h = 0

Combine like terms: 6 + -4 = 2

2 + -2.7h + -1.3h = 0

Combine like terms: -2.7h + -1.3h = -4h

2 + -4h = 0

Solving

2 + -4h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2' to each side of the equation.

2 + -2 + -4h = 0 + -2

Combine like terms: 2 + -2 = 0

0 + -4h = 0 + -2

-4h = 0 + -2

Combine like terms: 0 + -2 = -2

-4h = -2

Divide each side by '-4'.

h = 0.5

Simplifying

h = 0.5


You're welcome! C:

User Mbroadst
by
5.7k points